2020
DOI: 10.21512/jas.v7i2.5780
|View full text |Cite
|
Sign up to set email alerts
|

Implementing SDG to Village Level by Integrating Social Capital Theory and Value Chain: (Case of Village Tourism Pentingsari in Yogyakarta, Indonesia)

Abstract: Since the publication of the 2030 blueprint, Sustainable Development Goals (SDGs) have been promoted as a global project. Many steps have been taken; however, until now, the achievement remains limited. This is due to the low understanding of SDGs from stakeholders at the local level, such as the village. This study examines how we can develop SDG awareness and implementation in the village level. This article argues that we need to look at two essential factors namely the notion of social capital and value ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, the interaction of multiple stakeholders still needs more attention and critical study. This has been initiated in a study conducted by Affandi et al (2020), which states that stakeholders at the local level still have a low level of understanding regarding sustainable development. As a result, it is important to consider the idea of social capital and management value chains to achieve sustainable performance at the local level.…”
Section: Stakeholder Interaction and Special Attention For Indigenous Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…However, the interaction of multiple stakeholders still needs more attention and critical study. This has been initiated in a study conducted by Affandi et al (2020), which states that stakeholders at the local level still have a low level of understanding regarding sustainable development. As a result, it is important to consider the idea of social capital and management value chains to achieve sustainable performance at the local level.…”
Section: Stakeholder Interaction and Special Attention For Indigenous Peoplementioning
confidence: 99%
“…To optimize this potential, the stakeholders must be able to create solid social bounding within the community. At this stage, social capital is needed to involve the community in taking an active role in the development activities (Affandi et al 2020).…”
Section: Stakeholder Interaction and Special Attention For Indigenous Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Yogyakarta, especially in the coastal area, so that the management, utilization, and control of the province's strategic areas, especially related to the potential for marine tourism in support. Research conducted by [12] related to the implementation of SDGs relates at the village level through the integration of social capital theory and value chains in the Tourism Village of Pentingsari Village in the Special Province of Yogyakarta, the results of the study show that local leaders can mobilize social capital to socialize the importance of SDGs at the village level. Value chain management allows local leaders to manage sustainable economic activities at the village level to improve the implementation of SDGs at the village level.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Sunkar et.al (2016) in Cibalay Megalithic site, West Java province, has found that social capital in the form of trust becomes the crucial element that would enhance the community lives and conserve the cultural heritagebased tourism (Sunkar et al, 2016). Moreover, Affandi et al (2016) emphasized that social capital should become the main foundation when it comes to implementing Sustainable Development Goals in the context of tourism village enhancement such as Pentingsari, Mangunan, and Bleberan village in Yogyakarta province (Affandi, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%